SAVING BEHAVIORS MODEL OF EARLY ADULTHOOD IN BANGKOK METROPOLIS - Jakkrit Dhanadith1, Asst.Prof.Dr.Sudawan Somjai2 and Pornkul Suksod3 (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Savings are economically important. Savings were also impacted the quality of life and stability of living in the elderly. Therefore, encouraging people to have more saving behaviors for the benefits of the nation, society and people. The research objectives were to: 1) study the important level of saving behaviors in early adulthood; 2) study the influence of financial institution role, financial literacy, economic status, and personal psychology affecting the saving behavior of the early adulthood; and 3) present the model of the saving behavior in early adulthood in Bangkok Metropolis. Using mixed research which is quantitative research and qualitative research. The quantitative research sample consisted of 320 people aged 21-40 years, domiciled in Bangkok, obtained from stratified sampling. The research instrument was a questionnaire. Data were analyzed by using a structural equation model. Qualitative research used an in-depth interview with a total of 18 key informants were; 1) eight executives of government and private financial institutions; and 2) ten people with savings and investment experience. The results of the research; 1) the saving behavior in early adulthood was at the most important level; 2) the economic status, personal psychology, financial literacy, and the role of financial institutions, there was a significant positive direct influence on the saving behavior of the early adulthood at p< .05, respectively; and 3) the saving behavior model of the early adulthood in Bangkok Metropolis consisted of: (1) awareness of the importance and positive attitude towards saving; (2) education and training on finance and investment to increase the knowledge and the understanding of the savings; (3) determining the savings ratio and selecting the type of savings that corresponds to income; (4) allocating income for investments that are appropriate to one's economic potential and position; and (5) consider and accept any risks associated with that investments that can self-regulation in order to attain consistent saving behavior. Therefore, government and financial institutions should provide knowledge, create understanding, and financial literacy, and saving education among all age groups in order to create awareness, and perceive the importance value of saving and leading to more saving behaviors in the people's sector. Keywords: Saving Behaviors / Early Adulthood /Financial institute/ financial literacy